2021
DOI: 10.1155/2021/1056622
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Analysis and Integration of Transcriptome and Proteome Results Identify Key Coding and Noncoding Genes Predicting Malignancy in Intraductal Papillary Mucinous Neoplasms of the Pancreas

Abstract: Background. Intraductal papillary mucinous neoplasms (IPMNs) are precursor lesions of pancreatic ductal adenocarcinoma (PDAC). IPMNs are generally associated with high risk of developing malignancy and therefore need to be diagnosed and assessed accurately, once detected. Existing diagnostic methods are inadequate, and identification of efficient biomarker capable of detecting high-risk IPMNs is necessitated. Moreover, the mechanism of development of malignancy in IPMNs is also elusive. Methods. Gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Elena Vila Navarro et al [32] sequenced and validated the miRNAs used to detect pancreatic tumors and found that hsa-miR-4770 was signi cantly upregulated in pancreatic ductal adenocarcinoma, and identi ed hsa-miR-4770 as one of the novel markers with potential diagnostic or therapeutic value. In addition, hsa-miR-4770 was upregulated in pancreatic intraductal papillary mucinous neoplasms [33]. Metastasis associated lung adenocarcinoma transcript 1 (MALAT1) is overexpressed in malignant retinoblastoma (RB), the ceRNA network was constructed between MALAT1 and cytokinesis-associated genes, and hsa-miR-4770 was found as one of the potential miRNAs involved in the association of MALAT1 and RB [34].…”
Section: Discussionmentioning
confidence: 99%
“…Elena Vila Navarro et al [32] sequenced and validated the miRNAs used to detect pancreatic tumors and found that hsa-miR-4770 was signi cantly upregulated in pancreatic ductal adenocarcinoma, and identi ed hsa-miR-4770 as one of the novel markers with potential diagnostic or therapeutic value. In addition, hsa-miR-4770 was upregulated in pancreatic intraductal papillary mucinous neoplasms [33]. Metastasis associated lung adenocarcinoma transcript 1 (MALAT1) is overexpressed in malignant retinoblastoma (RB), the ceRNA network was constructed between MALAT1 and cytokinesis-associated genes, and hsa-miR-4770 was found as one of the potential miRNAs involved in the association of MALAT1 and RB [34].…”
Section: Discussionmentioning
confidence: 99%
“…Some reports found tumor-specific upregulation of various types of small noncoding RNAs (ncRNAs), such as small nuclear RNAs, Piwi-interacting RNAs and long ncRNAs (lncRNAs) like HOTAIR and MALAT1. They act as diagnostic and prognostic markers in the serum or plasma of cancer patients[ 84 , 85 ]. Amidst that, some have reported alterations in gene expression according to disease progression, which discriminates between a chronic inflammatory state and carcinoma (Table 3 )[ 86 , 87 ].…”
Section: Cfdna and Its Associated Secreted Proteomementioning
confidence: 99%
“…There were key changes in gene expression between low-risk and high-risk IPMNs. However, 12 genes were altered significantly, and the so-called “12-gene signature” has been proposed as a potential biomarker in the pancreatic juice for the identification of IPMNs that have a high risk for malignant development [ 26 ]. The key signaling pathways or protein complexes involved in the pathogenesis of IPMNs include G-protein-coupled receptor (GPCR), transforming growth factor (TGF), SWI/SNF, WNT and phosphatidylinositol 3-kinase (PI3K) [ 27 ].…”
Section: Genomic Profiling – Molecular Alterationsmentioning
confidence: 99%
“…There were key changes in gene expression between low-risk and high-risk IPMNs. However, 12 genes were altered significantly, and the so-called "12-gene signature" has been proposed as a potential biomarker in the pancreatic juice for the identification of IPMNs that have a high risk for malignant development [26].…”
Section:  Genomic Profiling -Molecular Alterationsmentioning
confidence: 99%